Population Dynamics of the Mackenzie Delta Reindeer Herd, 1938-1958 - Krebs, Charles J. (ARCTIC, 1961)
Analyzes fluctuations in the size of both government- and Eskimo-owned herds of Rangifer tarandus in the Reindeer Grazing Preserve of northern Mackenzie District. Each of the six Eskimo-owned herds increased in numbers for a few years, then declined and ultimately, except one, was returned to the nucleus, government herd. Annual variation in herd size is examined in relation to the birth, death, and dispersal rates. The last which represents losses by straying, approx. 17,000 since 1938, usually yearlings, is the most important, birth rate the least. Effects of herd size and composition (tabulated by age and sex) on the birth and dispersal rates are deemed negligible. Dispersal is apparently caused by factors extrinsic to the herd itself, e.g. insects, weather, man, and their interactions.